An RFID-Based Validation System for Halal Food - Nasir, M.; Norman, A.; Fauzi, S.; Azmi, M. (ZARKA PRIVATE UNIV, COLLEGE COMPUTING & INFORMATION TECHNOLOGY, PO BOX 2000, ZARQA, 13110, JORDAN, 2011)
In recent years, Muslims have depended on the Halal logo, displayed on food packaging, to indicate that the products are prepared according to Halal precepts. As laid out in the Quran, Halal designates that which is lawful and permitted. However, due to the rapid development of advanced technology and the stringent procedures legislated by the Department of Islamic Development in Malaysia, manufacturers may sometimes resort to fabricating a fake logo to attract Muslim consumers. This study is focused on validating Halal status for food products by using radio frequency identification technology to enhance existing methods in Malaysia. A preliminary survey was carried out to evaluate the industry's readiness to implement radio frequency identification technology in Malaysia. A process model and prototype were developed to enhance existing systems. Through this new approach, the authentic Halal logo that is issued by JAKIM can easily be validated, because every stamp that will be embedded into food packages is identified with its own unique identification number. An radio frequency identification reader will be placed in retail venues for consumers to validate their food's Halal status. User evaluation has been conducted to measure satisfaction in terms of usability, efficiency, security, affordability and profitability. Based on the evaluation, all respondents are satisfied with the performance of this new technology and fully support implementing this system globally, as the Malaysian government is now moving towards becoming the world's Halal hub.